Kenaikan Harga Minyak Goreng dalam Perspektif Hukum Persaingan Usaha dan Ekonomi - Andi Nova Bukit; Uswatun Hasanah; Khairun Na’im; Elyani Elyani (Jurnal Justisia : Jurnal Ilmu Hukum, Perundang-undangan dan Pranata Sosial, 2022)
The current increase in cooking oil prices greatly affects purchasing power and greatly impacts the community's economy. Various ways have been taken by the government to suppress the rate of cooking oil prices, ranging from issuing a ministerial regulation of trade to cooking oil subsidies. However, these policies have not been able to suppress the rate of cooking oil prices. This study is carried out to analyze whether there are cartel practices that have caused the current soaring cooking oil prices, as well as their impact on the economy. The research was conducted using a normative juridical method with the results of the study. It is strongly suspected that the existence of cartel practices caused this situation to continue. Based on the findings made by the KPPU, namely the discovery of evidence of alleged violations of articles 5, 11, and 19 letter c of Law No. 5/1999 where it is alleged that there has been an oligopoly practice of the national cooking oil market structure by fixing prices and regulating production. However, there are some shortcomings in Law no. 5/1999 in ensnaring the perpetrators of this cartel is about the criteria for a cartel which has not yet been specifically defined, so it is not easy to win a cartel case in court.